Methodical Approaches to Creation of Dividing Automation at Industrial Enterprises with Generating Power Plants - E. V. Kalentionok; Y. D. Filipchik (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2010)
The paper considers a problem pertaining to creation of dividing automation at industrial enterprises which have their own generating plants. Algorithms for action of dividing automation that permit to ensure minimum possible power non-balance while using generating plants for autonomous operation and possible parameters for its response are proposed in the paper.